K(ATP) channels in the nodose ganglia mediate the orexigenic actions of ghrelin - Grabauskas, Gintautas (J Physiol, 2015)
ABSTRACT: Ghrelin is the only known hunger signal derived from the peripheral tissues. Ghrelin overcomes the satiety signals evoked by anorexigenic molecules, such as cholecystokinin (CCK) and leptin, to stimulate feeding. The mechanisms by which ghrelin reduces the sensory signals evoked by anorexigenic hormones, which act via the vagus nerve to stimulate feeding, are unknown. Patch clamp recordings of isolated rat vagal neurons show that ghrelin hyperpolarizes neurons by activating K(+) conductance. Administering a K(ATP) channel antagonist or silencing Kir6.2, a major subunit of the K(ATP) channel, abolished ghrelin inhibition in vitro and in vivo. Patch clamp studies show that ghrelin inhibits currents evoked by leptin and CCK-8, which operate through independent ionic channels. The inhibitory actions of ghrelin were abolished by treating the vagal ganglia neurons with pertussis toxin, as well as phosphatidylinositol 3-kinase (PI3K) or extracellular signal-regulated kinase 1 and 2 (Erk1/2) small interfering RNA. In vivo gene silencing of PI3K and Erk1/2 in the nodose ganglia prevented ghrelin inhibition of leptin- or CCK-8-evoked vagal firing. Feeding experiments showed that silencing Kir6.2 in the vagal ganglia abolished the orexigenic actions of ghrelin. These data indicate that ghrelin modulates vagal ganglia neuron excitability by activating K(ATP) conductance via the growth hormone secretagogue receptor subtype 1a–G(αi)–PI3K–Erk1/2–K(ATP) pathway. The resulting hyperpolarization renders the neurons less responsive to signals evoked by anorexigenic hormones. This provides a mechanism to explain the actions of ghrelin with respect to overcoming anorexigenic signals that act via the vagal afferent pathways. KEY POINTS: Ghrelin, a hunger signalling peptide derived from the peripheral tissues, overcomes the satiety signals evoked by anorexigenic molecules, such as cholecystokinin (CCK) and leptin, to stimulate feeding. . Using in vivo and in vitro electrophysiological techniques, we show that ghrelin hyperpolarizes neurons and inhibits currents evoked by leptin and CCK-8. . Administering a K(ATP) channel antagonist or silencing Kir6.2, a major subunit of the K(ATP) channel, abolished ghrelin inhibition. . The inhibitory actions of ghrelin were also abolished by treating the vagal ganglia neurons with pertussis toxin, as well as phosphatidylinositol 3-kinase (PI3K) or extracellular signal-regulated kinase 1 and 2 (Erk1/2) small interfering RNA. . Feeding experiments showed that silencing Kir6.2 in the vagal ganglia abolished the orexigenic actions of ghrelin. . These data indicate that ghrelin modulates vagal ganglia neuron excitability by activating K(ATP) conductance via the growth hormone secretagogue receptor subtype 1a–G(αi)–PI3K–Erk1/2–K(ATP) pathway. . This provides a mechanism to explain the actions of ghrelin with respect to overcoming anorexigenic signals that act via the vagal afferent pathways. .